Interference of goethite in the effects of glyphosate and Roundup® on ZFL cell line - Silva, Natara D.G.da; Carneiro, Cristiane E.A.; Campos, Estefânia V. R; Oliveira, Jhones L. de; Risso, Wagner E.; Fraceto, Leonardo, F.; Zaia, Dimas A. M.; Martinez, Cláudia B. R. (Elsevier, 2020)
Goethite (α-FeOOH) brings important perspectives in environmental remediation, as, due to its physicochemical properties, this iron oxide can adsorb a wide variety of compounds, including glyphosate. This study aimed to evaluate the effects of goethite nanoparticles (NPs), glyphosate (Gly), Roundup® (Rd), and co-exposures (Gly + NPs and Rd + NPs) on zebrafish liver cell line (ZFL). ZFL cells were exposed to NPs (1, 10, and 100 mg L−1), Gly (3.6 mg L−1), Rd (10 mg L−1), and co-exposures (Gly + NPs and Rd + NPs), or only to saline for 1, 6, and 12 h. Cell viability was assessed by Trypan blue, MTT, and neutral red assays. The generation of reactive oxygen species and total antioxidant capacity were also determined, while genotoxicity was quantified by the comet assay. Both NPs and Rd in isolation produced cytotoxic effects at 6 h and genotoxic effects at 1 and 6 h. Rd + NPs resulted in synergistic effects, intensifying the toxicity. Cells exposed to Gly did not present toxic effects and Gly + NPs resulted in the suppression of toxic effects observed for NPs. The presence of other components in Roundup® seems to favor its toxicity compared to the active ingredient. In conclusion, according to the in vitro model, the concentrations used were not safe for the ZFL lineage.
Keywords: Iron oxide; Nanotoxicology; In vitro assays; Danio rerio; Cell viability; DNA damage